Analysis of Nursing Workload at Islamic Hospital Surabaya - Kartini, Yanis; Nursalam, Nursalam; Ahsan, Ahsan; Novent, Iis; Sulastri,; Nurhayati, Uci (International Journal of Psychosocial Rehabilitation, 2020)
An easy access to receive health services through BPJS (The Healthcare and Social Security Agency) will increase the number of patients coming to a hospital for both inpatient and outpatient medical treatments. The increasing number is dominated by the elderly (70%). This condition has impacts on the nurses’ workload. This study aimed to analyze the correlation between the types of hospital wards, nurses’ work shift and workload in the in-patient wards of Rumah Sakit Islam Surabaya. This condition affects their workload. This study aimed to analyze the correlation between the types of hospital wards, nurses’ work shift and workload in the in-patient wards of Rumah Sakit Islam Surabaya. This study used a descriptive analytic research design with a cross-sectional approach. The population of all nurses in the in-patient wards of the stated hospital totaled 109 nurses of whom 83 respondents were chosen using a cluster random sampling technique. The variables included the types of wards, nurses’ work shifts and workloads. The data were collected using an observation sheet. The data were analyzed using a Chi-square test with a level of significance α = 0.05. The Chi-square test revealed that there was a correlation between work shift and workload in which ρ (0.036) < α (0.05), whereas the types of wards did not correlate with workload shown by the result that ρ (0.341) > α (0.05). In conclusion, work shift correlates with workload. Therefore, proportional work scheduling should be considered to fulfil the patients’ needs and prevent tiredness due to high workload.